Pengaruh Motivasi, Gaya Hidup an Kepercayaan Konsumen terhadap Keputusan Pembelian di Facebook Marketplace: : Studi Kasus pada Mahasiswa Kampus Negeri di Kota Medan - Annisa Aprilia; Sri Ramadhani; Nuri Aslami (Masyarakat Ekonomi Syariah Bogor, 2023)
The purpose of this study was to see how motivation, lifestyle, and consumer confidence affect purchasing decisions on Facebook Marketplace (Case Study on State Campus Students in Medan City). Purchase decision is the dependent variable, while motivation, lifestyle and consumer confidence are independent factors. The information used was collected directly from state university students in the city of Medan. The data regression panel was used to analyze the data in this study, which was carried out using SPSS 25 software. The sample in this study consisted of 105 samples collected using a purposive sampling strategy. Keywords: Motivation, Lifestyle, Consumer Confidence, Purchase Decision, Facebook Marketplace.